STUDIES ON RADIATION PASTEURISATION OF MEDIUM FATTY FISH III. STORAGE PROPERTIES OF WHITE POMFRET(Stromateus cinereus ) FILLETS - KAMAT, S V; GAONKAR, S. G; KUMTA, U S (Fishery Technology, 2025)
White pomfret fillets packed under aerobic conditions hada limited shelf life of 8 days as against 10 days for samplespacked under vacuum and stored at 0~2Â°C. Irradiation and subsequentstorage of the fillets under vacuum at 0-2Â°C exhibitedshelf lives of 30, 50 and 60 days for radiation doses of 0.1,0.3 and 0.5 Mrad respectively in contrast to aerobically packedfillets which showed only 20, 35 and 50 days of storage life forthe same levels of radiation doses and developed yellow discolourationand rancid odours.